Predictors of nutritional and inflammation risk in hemodialysis patients - Sá Martins, V (2020)
Background: Malnutrition and chronic inflammation are prevalent complications in hemodialysis (HD) patients. Different nutritional assessment tools are used to identify patients at risk. A composite and comprehensive malnutrition inflammation score (MIS) has been correlated with morbidity and mortality, and appears to be a robust and quantitative tool. Objectives: Determine malnutrition risk profile in a sample of portuguese HD patients; determine the association of clinical and laboratory factors with MIS, and the impact of each parameter on MIS. Methods and results: We performed, between September 15th of 2015 and January 31st of 2016, a cross sectional analysis of 2975 patients, representing 25% of portuguese HD patients. 59% were men (66.7 ± 14.8 years); 31% diabetic; 79% and 21% performed, respectively, high-flux HD and HDF. A MIS >5 was considered to indicate higher risk and was present in 1489 patients (50%). Amongst all parameters, comorbilities/dialysis vintage, transferrin, functional capacity, changes in body weight and decreased fat stores showed the higher impact, while albumin had one of the lowest impact on the nutritional risk. Multivariable analysis: Higher age (>75 years, OR 1.71, p < 0.001), diabetes (OR 1.25, p = 0.026), lower P levels (OR 1.57,p = 0.001), higher Ca levels (OR 1.51, p < 0.001), higher ERI (OR 1.05, p < 0.001), higher Kt/V (OR 2.14, p < 0.001) and higher CRP (OR 1.01, p < 0.001) were independently associated with a higher risk of MIS>5; higher nPNA (OR 0.29, p < 0.001) and higher Pcreat (OR 0.88, p < 0.001) were associated with a risk reduction of MIS>5 (95% CI). Conclusions: Routine clinical and analytic parameters were found to be associated with MIS range that might indicate higher risk, and may represent a simple alert sign for the need of further assessments. (c) 2019 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism